2019
DOI: 10.1021/acs.jafc.9b03063
|View full text |Cite
|
Sign up to set email alerts
|

Monoacylglycerol of 7,10-Dihydroxy-8(E)-octadecenoic Acid Enhances Antibacterial Activities against Food-Borne Bacteria

Abstract: Conversion of free fatty acids into monoacylglycerol gives rise to new structural properties, particularly amphipathic property. Therefore, monoacylglycerols are widely used in pharmaceutical and food industries and are also reported to facilitate better absorption into the human body. A functional fatty acid when transformed into a monoacylglycerol will possibly conserve both the original functionality and amphipathic property. The compound 7,10-dihydroxy-8(E)octadecenoic acid (DOD) was generated from oleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The multivariate analysis of P. aeruginosa isolation also suggested that octadecenoic acid and phenol might be the most important independent factors influencing the P. aeruginosa isolation. The upregulated level of octadecenoic acid in patients with P. aeruginosa isolation might be associated with its antibacterial activity ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate analysis of P. aeruginosa isolation also suggested that octadecenoic acid and phenol might be the most important independent factors influencing the P. aeruginosa isolation. The upregulated level of octadecenoic acid in patients with P. aeruginosa isolation might be associated with its antibacterial activity ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are γ -sitosterol (25.76%), n -hexadecanoic acid (4.27%), and ( Z )-11-octadecenoic acid (3.16%) that are reported as potent broad-spectrum antimicrobials [ 38 42 ]. Moreover, SPE has antimicrobial effect against both Gram-positive and Gram-negative bacteria due to the presence of carvacrol (0.57%) confirmed by Memar et al .…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesized NS from I. oblongifolia is rapid, cheap and ecofriendly and also could suppress the induced parasitemia on day 7 postinfection with P. chabaudi . This is due to the presence of active compounds like octadecenoic acid and 2,6-di-t-butyl-p-benzoquinone in the I. oblongifolia leaves ( Chen et al, 2019 , Dkhil et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%